Penggunaan Antibiotik yang Kurang Tepat pada Peternakan Babi di Kota Kupang, Nusa Tenggara Timur - Detha, Annytha Ina Rohi; Wuri, Diana Agustiani; Ramos, Filomena; Biru, Desi; Lakapu, Anita; Meha, Margie Mila (Jurnal Veteriner; Vol 22 No 2 (2021)DO - 10.19087/jveteriner.2021.22.2.162, 2021)
Misuse of antibiotics has the potential to accelerate the emergence of types that are resistant to inappropriate drugs. This study aims to evaluate the inappropriate use of antibiotics in pig farms in the City of Kupang, East Nusa Tenggara. This antibiotic use evaluation study was conducted from March to May 2018. This study was conducted on 100 pig farmers spread across 6 (six) districts in Kupang City. The sampling technique was done by stratified random sampling method based on the characteristics or types of the population. This research used descriptive analysis method from the results of questionnaire data collection that had been filled out by pig farmers in Kupang City. Based on the results obtained that 84% of pig farmers or respondents did not know the function of antibiotics, and 83% of respondents did not know that the administration of antibiotics must be done with the supervision of a veterinarian. The results also showed that 86% of pig farmers buy antibiotics without a veterinarian’s prescription, with the type of antibiotics most often used were the tetracycline and sulfonamide groups. These results conclude that dominant respondents apply antibiotics without veterinary supervision, which can contribute to the spread of resistant bacteria so that it adversely affects human health.